The Adat Litigation and Adultery Sanctions In Batanghari-Jambi Province - Fathuddin Abdi (Jurnal Hukum Islam, 2020)
This paper analyzes about the process and sanctions for adultery in the Customary institutions of Batanghari according to Islamic law. The method used sociology of law with a qualitative approach. The technique of collecting information uses observation, interviews and literary studies. The analysis technique uses an interactive model. The results showed, the resolution process and sanctions adultery in the Customary Institution of Batanghari, are:1) adultery pairs will be called by customary stakeholders (niniek mamak) and collected by tuo-tuo tenganai;2) if both have confessed, the niniek mamak, syara’ officials and the village head will determine the sanctions in the form of fines/debts and the time of 236 │ Covid-19 Pandemic as the Reasoning of Force Majeure Towards Financing ... (Riska Wijayanti) Vol 18 No 2, Desember 2020 ISSN 1829-7382 (Print) 2502-7719 (Online) payment; 3) payment times: 1x7, 2x7, 3x7 (3 weeks). If, the perpetrator has not paid, then he will be expelled from the village, because it is considered that he does not respect customary law. The sanctions for the perpetrator of adultery in that customary law is not the same as the Islamic criminal law, namely the stoning penalty for adultery. However, substantively its does not contradict Islamic law because the Al-Quran and Sunnah do not show the prohibition of imposing sanctions that are less than the ones stipulated by sharia, even Islamic law calls for the perpetrator to be forgiven or to be given a punishment that does not exceed the perpetrator's actions.